Relationship Between Mathematics Anxiety and Use of Emotion Regulation Strategies in Young Adults - Sood, Vasudha (My University, 2017)
Mathematics anxiety, the debilitating emotional reaction to mathematics, involving a feeling of nervousness, can have harmful effects for mathematics achievement in students. Though there is an upsurge of interest in emotion regulation research, the way the emotion regulation functions in relation to specific emotions remains unelaborated. The present study focuses on the relationship between mathematic anxiety and the use of emotion regulation strategies in young adults. A sample of 160 student volunteers (80 males and 80 females) of the age range 18-25 yrs participated in this study. It was hypothesized that females show high mathematics anxiety as compared to males. In addition to this it was also predicted that high math anxiety individuals use more of expressive suppression and low math anxiety individuals use more of cognitive reappraisal emotion regulation. Gender differences in emotion regulation were also investigated. The findings of the studies confirmed all the hypotheses posited except the first one where no difference between males and females in mathematic anxiety was observed. High math anxiety group used expressive suppression and low math anxiety group used cognitive reappraisal emotion regulation. And also males used more of cognitive reappraisal and females used more of expressive suppression emotion regulation.
Keywords: Mathematics anxiety, Emotion regulation strategies, Gender